The palliative care experience in Irish nursing homes during the COVID-19 pandemic: a survey of residents, family, and staff - Owen Doody; John Lombard; Tara Delamere; Mary Rabbitte (BMC Palliative Care, 2024)
Abstract Background Nursing homes and other long-term care services account for a disparate share of COVID-19 cases and casualties worldwide. During COVID-19 there is a distinct need to preserve a holistic view of the wellbeing of residents of nursing homes, be mindful of their rights as citizens, and to be aware of protecting residents from infection. The delivery of health and social care throughout a pandemic must remain person-centred and adhere to a human rights-based approach. Methods This study aimed to capture nursing home residents, their families and staff’s perspective of the nursing homes residents experience, approaches of staff and the nursing home environment. An online survey was distributed via stakeholder networks and online platforms across Ireland. This study was performed and reported in line with the Consensus-Based Checklist for Reporting of Survey Studies (CROSS). Results 25 residents, 42 family members and 51 staff completed the survey (n = 118). Across the domains measured all but one aspect scored above 50% (residents get up and go to bed when they want 41.5%) with the highest score of 89.1% scored for the nursing home is comfortable and well-kept. Results highlight evidence of positive experiences and endeavours to preserve social connections, residents were in a safe place cared for by staff who did their best in a difficult position and who went above and beyond their duty of care. However, some families reported poor communication, no internet connections, not enough phones or tablets, and that staff were busy and unable at times to assist residents who needed help using phones/tablets. Conclusion This study highlights the importance of human rights and how they ought to inform and shape the advancement of public health advice and policy documents. Overall, nursing home residents, their families and staff reported favourably on the study measures. However, issues pertaining to communication are essential and there is a need to address issues such as the provision of accurate timely information, communication infrastructure and resources, and inconsistencies in communications. Of note is that while healthcare professionals have a duty to uphold the rights of nursing home residents, they themselves have human rights which must also be protected and supported.